2012
DOI: 10.1111/j.2044-8295.2012.02108.x
|View full text |Cite
|
Sign up to set email alerts
|

Family emotion expressivity, emotion regulation, and the link to psychopathology: Examination across race

Abstract: Research has established links between parental emotion socialization behaviours and youth emotional and psychological outcomes; however, no study has simultaneously compared these relations for White, Black, and Asian individuals. In this study, emerging adults identifying as White (n= 61), Black (n= 51), or Asian (n= 56) retrospectively reported on parents' emotion socialization behaviours during childhood, existing emotion regulation (ER) skills, and current psychopathology symptoms. Asian participants repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 58 publications
(95 reference statements)
1
42
0
2
Order By: Relevance
“…The predominantly female sample is a limitation; however, given the statistically significant findings, it is unlikely that this sample limitation affected our ability to detect moderating effects by youth gender. It is unclear whether the same associations and pathways would be replicated in a more racially or culturally diverse group (e.g., Morelen, Jacob, Suveg, Jones, & Thomassin, 2013). Future studies could also explore the potential impact of socioeconomic status or other risk factors (for examples of such work, see Fainsilber Katz et al, 2016, andZeman, Dallaire, &Borowski, 2016); diversity in family composition (for a study of ES in single mother headed households, see McKee et al, 2015); and other socializing agents such as siblings, peers, and educators (see, e.g., Klimes-Dougan et al, 2014) on ES processes.…”
Section: Discussionmentioning
confidence: 99%
“…The predominantly female sample is a limitation; however, given the statistically significant findings, it is unlikely that this sample limitation affected our ability to detect moderating effects by youth gender. It is unclear whether the same associations and pathways would be replicated in a more racially or culturally diverse group (e.g., Morelen, Jacob, Suveg, Jones, & Thomassin, 2013). Future studies could also explore the potential impact of socioeconomic status or other risk factors (for examples of such work, see Fainsilber Katz et al, 2016, andZeman, Dallaire, &Borowski, 2016); diversity in family composition (for a study of ES in single mother headed households, see McKee et al, 2015); and other socializing agents such as siblings, peers, and educators (see, e.g., Klimes-Dougan et al, 2014) on ES processes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the links between PA and depression should be interpreted in light of our predominantly European American sample. Prior research shows experiencing PA varies by culture (Leu, Wang, & Koo, 2011), as do the links between PA and adjustment (Morelen, Jacob, Suveg, Jones, & Thomassin, 2013).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Third, the links between parents' emotional expression and children's regulation have yet to be tested in Asian American families, and researchers have yet to include both self-reported and observed components of parental emotion expression in these investigations. A cross-cultural study showed that college students' ratings of positive parental emotion were associated with fewer emotion-regulation difficulties (Morelen, Jacob, Suveg, Jones, & Thomassin, 2013), but these associations were only found among White students. Furthermore, although previous research with European American samples showed a modest agreement between observed and self-reported measures of parent emotion (Eisenberg, Gershoff, et al, 2001), based on the theoretical models reviewed here, there is reason to suspect that these findings might not generalize to Asian American families.…”
Section: Cultural Orientation Parental Emotion Expression and Childmentioning
confidence: 99%